Towards a multi-criteria framework for stereotomy – Workflows for subtractive fabrication in complex geometries. Issue 3 (13th August 2018) - Fernando, Shayani; Weir, Simon; Reinhardt, Dagmar; Hannouch, Adam
Graphical abstract: Abstract: In a context of stereotomy, robotic subtractive cutting enables design-to-production processes that integrate craftsmanship with advanced manufacturing technology. This paper discusses empirical research into the fabrication of complex and custom-designed geometries by means of robotic subtractive cutting, with a specific focus on modular elements and joint typologies that form an essential condition for self-supporting stone structures. The paper presents research findings in two parts. In the first part, four case studies for jointing techniques and a cross-comparison between these are introduced to derive strategies for multiple criteria, including macro-and-micro geometries, modules and joints, structural performance, material variations, machine cutting methods and end-effectors, and robotic workspace. In the second part, the paper focuses on the structural performance of the joint geometry typologies, expanded towards material constraints and robotic fabrication process. The paper concludes with a discussion on these varied subtractive cutting methodologies and a resulting design-to-fabrication workflow, and indicates future research work.